Outcomes of the advanced visualization in corneal surgery evaluation trial; a non-inferiority randomized control trial to evaluate the use of intraoperative OCT during Descemet membrane endothelial keratoplasty - Muijzer, Marc B.; Delbeke, Heleen; Dickman, Mor M.; Nuijts, Rudy M.M.A.; Noordmans, Herke Jan; Imhof, Saskia M.; Wisse, Robert P. L. (Frontiers in Ophthalmology, 2023)
Objective To evaluate if an intraoperative-OCT (iOCT) optimized surgical protocol without prolonged overpressure is non-inferior to a standard protocol during Descemet membrane endothelial keratoplasty (DMEK). Methods Sixty-five pseudophakic eyes of 65 patients with Fuchs endothelial dystrophy scheduled for routine DMEK were recruited in this prospective non-inferiority international multicenter randomized control trial. Subjects were randomized to the control arm (n=33) without iOCT-use and raising the intraocular pressure above normal physiological limits for 8 minutes (i.e., overpressure) or the intervention arm (n=32) with OCT-guidance to assess graft orientation and adherence, while refraining from prolonged overpressure. The primary outcome was the incidence of postoperative surgery-related adverse events (AE). The non-inferiority margin was set at a risk difference of 10%. Secondary outcomes included iOCT-aided surgical decision making, surgical times, and endothelial cell density (ECD) corrected distance visual acuity (CDVA) at 6 months follow-up. Results In the intervention group, 12 subjects developed 13 AEs compared to 13 AEs in 10 subjects in the control group (P=0.644). The risk difference measured -0.32% (95%CI: -10.29 – 9.84). The ECD and CDVA did not differ between the two groups 3 and 6 months postoperatively (P=>0.05). Surgeons reported that iOCT aided surgical decision-making in 40% of cases. Surgery and graft unfolding time were, respectively, 13% and 27% shorter in the iOCT-group. Conclusions iOCT-guided DMEK surgery with refraining from prolonged over-pressuring was non-inferior compared to conventional treatment. Surgery times were reduced considerably and iOCT aided surgical decision-making in 40% of cases. Refraining from prolonged overpressure did not affect postoperative ECD or CDVA. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT03763721 (NCT03763721).